Between science & rejectionism : the vaccine dilemma - Abu Bakar, Asrar (2019)
In modern medical times, one of the biggest challenges among the medical fraternity is the resurgence of vaccine refusal among parents. We are now seeing a spike in vaccine preventable diseases in an age where certain childhood infectious diseases were at some point almost disappearing. This presentation focuses on the issues the medical community is facing along with root cause analysis of vaccine rejectionism and the dilemmas surrounding it.